The effect of foam rolling on the heart rate recovery of Filipino rowers - Sha, Kharl Julianne B. 1999-; Valleser, Christian Wisdom M. MSHMS (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2023)
The aim of this research is to examine the effect of foam rolling on the heart rate recovery in four in-season rowers. (2 male, 2 female) The heart rates of the participants were measured after the maximal phase of the rowing training and a minute after to measure heart rate recovery. On one of the two testing days with a one-week gap, the participants performed a foam rolling intervention prior to rowing training. The FR intervention consisted of rolling the quadriceps, adductors, hamstrings, iliotibial band, and glutes for 2 sets of 30 seconds alternate sides, and with a 30 second rest before proceeding to the next muscle group. In comparing the heart rate recovery of the rowers with and without the FR intervention, no significant differences were observed at 0.05 level of significance. FR did not induce acute effects on the heart rate recovery of the rowers during rowing training. However, two participants observed positive feelings in training after performing the FR routine. In conclusion, FR did not affect HRR but may affect the psychological state of the athlete. Further studies on possible benefits of FR not only as a recovery support modality but as a factor in improving psychological state is encouraged.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Rowing -- Philippines; Rowers -- Philippines; Heart rate monitoring; Endurance sports